Note on feeding relationships of three species of cyprinid fish larvae in Al-Huwaiza marsh, Southern Iraq - Ahmed, S.M. (Mesopotamian Journal of Marine Sciences, 2022)
Food composition of three cyprinid larvae (Cyprinus carpio, Carassius auratus and Alburnus mosulensis) in Al-Huwaiza marsh has been studied during March and April 2006. The diet of these cyprinid larvae were consist mainly of zooplankton dominated by copepods both adult and larval stages followed by Cladocera Rotifera, aquatic insects and Ostracoda. The food of plant origin also exists and consists of diatoms and filamentous algae. Costello graphical plot showed that these larvae are generalist feeders. This strategy result in lower competition and allow these three species to co-occur in relatively high density in this marsh area. The food similarity between C. carpio and C. auratus was 0.60, between C. carpio and A. mosulensis was 0.44, while it was 0.72 between C. auratus and A. mosulensis. The food overlap analysis showed that C. carpio; C. auratus and A. mosulensis larvae share a wide range of prey types. Competition for food is possible However, direct competition seemed to be avoided to some extent as a result of great food availability in Al-Huwaiza marsh which makes it as a suitable nursery and feeding site for many cyprinid fish.